The challenges of emerging illness in urban environments: An overview - McCally, Michael (Springer-Verlag, 2001)
The New York City West Nile outbreak is an important case study for examining several medical and public health issues raised by the specter of emerging illnesses in urban areas. Five specific issues are addressed in this issue of theJournal of Urban Health: ecosystem health, vector (e.g., mosquito) control, risk communication, public health infrastructure, and parallels between this outbreak and bioterrorism.